Tensile strength evaluation of acrylic after ozonated water and microwave disinfection. - Hawraa Khalid Aziz (Universidad de Concepción., 2020)
Background: There is a need for safe disinfection methods without a detrimental effect on the acrylic denture base. Aim: the purpose of the current study was to evaluate the effect of ozonated water and two protocols of microwave disinfection on tensile bond strength of high-impact acrylic. Material and methods: Eighty samples were divided into four major groups: one control and three experimental groups, 20 specimens each. The experimental groups each received either disinfection by ozonated water, microwave 850W/1min, or microwave 650W/6min. Further division of the major groups into two sub-groups depending on the number of disinfection cycles and total immersion time in distilled water: One cycle and one day versus seven cycles and seven days. The control group specimens were immersed in distilled water without any disinfection for either one day or seven days. Tensile strength testing was performed on the specimens from the eight groups. The data were analyzed by SPSS version 21#. The ANOVA and Tukey-HSD multiple comparison tests were used for comparison for groups. Results: A non-significant difference in the tensile strength was observed in the groups subjected to one cycle of ozone or microwave disinfection at 850W/1min. There was a significant decrease in tensile strength for the specimens subjected to one cycle of 650W/6min microwaving. The number of testing cycles and storage time in distilled water had a significant impact on the tensile strength of the acrylic in all tested groups, by decreasing it. Conclusion: Ozone disinfection and microwaving at 850W for one minute did not affect the tensile strength of the acrylic, but repeated disinfection over seven days at one cycle per day impaired the tensile strength of the acrylic resin.